Dead Hand Proxy Puts and Hedge Fund Activism - Griffith, Sean J.; Reisel, Natalia (Journal of Financial and Quantitative Analysis, 2019)
We investigate the Dead Hand Proxy Put, a contractual innovation in corporate debt agreements that may impact hedge fund activism. We find the provision principally in loans, not bonds, and provide evidence linking the adoption of the provision to hedge fund activism. Furthermore, controlling for endogeneity, we find that the provision significantly reduces the cost of loans. Bondholder wealth also increases. Moreover, cross-sectional analysis of share returns reveals that the provision is positively associated with repeat banking relationships and negatively associated with free cash flow problems, suggesting a cost-benefit tradeoff.